2019
DOI: 10.32626/2227-6246.2019-13.46-55
|View full text |Cite
|
Sign up to set email alerts
|

The influence of kettlebell lifting training on the physical development of cadets of higher military educational institution

Abstract: Проблема фізичної підготовки майбутніх офіцерів Збройних Сил України, у той час, коли на сході нашої держави ведуться бойові дії за її незалежність, є достатньо актуальною та вимагає її подальшого розв'язання. У статті представлено результати перевірки ефективності методичної системи навчання гирьового спорту курсантів військових закладів вищої освіти щодо впливу занять гирьовим спортом на фізичний розвиток курсантів. Мета роботи-дослідити вплив занять гирьовим спортом за розробленою методичною системою на рів… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
3
0
8
Order By: Relevance
“…The results of indicator calculating showed the following average values of the PPCI: CG-1 -0.704 points, CG-2 -0.688 points, CG-3 -0.671 points. The obtained results confirm the data available in the scientific and methodological literature about the level of the PPCI of recruits and candidates for training in higher military educational institutions of Ukraine [7,17,18].…”
Section: Connection Of Thesupporting
confidence: 85%
See 1 more Smart Citation
“…The results of indicator calculating showed the following average values of the PPCI: CG-1 -0.704 points, CG-2 -0.688 points, CG-3 -0.671 points. The obtained results confirm the data available in the scientific and methodological literature about the level of the PPCI of recruits and candidates for training in higher military educational institutions of Ukraine [7,17,18].…”
Section: Connection Of Thesupporting
confidence: 85%
“…Many authors have observed the problem of the physical condition of young people in modern scientific literature [6][7][8][9][10][11]. Other scientists have studied the physical fitness, physical condition and health level of servicemen in Armed Forces, National Guard and other military formations of Ukraine [12][13][14][15][16][17][18]. Researchers decided that the problem of the deterioration of the physical condition of population was caused by a number of factors: insufficient level of physical activity, irrational nutrition, low material level, stressful nature of modern life, environmental pollution, low motivation for a healthy lifestyle [19][20][21].…”
Section: Connection Of Thementioning
confidence: 99%
“…Війська зв'язку включають вузлові та лінійні з'єднання, частини технічного забезпечення зв'язку та автоматизованих систем управління, служби фельд'єгерсько-поштового зв'язку [5, с. 3 Аналіз результатів наукових досліджень засвідчують, що в сучасних умовах якісно вирішувати будь-які завдання зможуть військовослужбовці з високим рівнем фізичної підготовки, психоемоційною стійкістю та працездатністю [4,6,12].…”
Section: науковий часопис нпу імені м п драгоманова Dragomanov Ukrain...unclassified
“…One of the ways to optimize the educational process in physical education is to search for rational approaches to physical education and health of students, the development of strength and strength endurance with the use of kettlebell lifting exercises in physical education lessons (Prontenko et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%